Twenty-Second Symposium on Biotechnology for Fuels and Chemicals 2001
DOI: 10.1007/978-1-4612-0217-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pretreatment Reagent and Hydrogen Peroxide on Enzymatic Hydrolysis of Oak in Percolation Process

Abstract: The effect of pretreatment reagent and hydrogen peroxide on enzymatic digestibility of oak was investigated to compare pretreatment performance. Pretreatment reagents used were ammonia, sulfuric acid, and water. These solutions were used without or in combination with hydrogen peroxide in the percolation reactor. The reaction was carried out at 170°C for the predetermined reaction time. Ammonia treatment showed the highest delignification but the lowest digestibility and hemicellulose removal among the three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Supplementation of cellulase with xylanase has been reported to enhance glucose release from pretreated biomass solids 36–38. Studies reported in the literature showed that glucose release is enhanced by xylose removal,39–46 and it has been argued that removing the hemicellulose coating on cellulose and/or its linkages with cellulose increases cellulose accessibility. However, Weimer et al47 suggested that intimate association of hemicellulose and cellulose does not inhibit cellulose digestion.…”
Section: Resultsmentioning
confidence: 99%
“…Supplementation of cellulase with xylanase has been reported to enhance glucose release from pretreated biomass solids 36–38. Studies reported in the literature showed that glucose release is enhanced by xylose removal,39–46 and it has been argued that removing the hemicellulose coating on cellulose and/or its linkages with cellulose increases cellulose accessibility. However, Weimer et al47 suggested that intimate association of hemicellulose and cellulose does not inhibit cellulose digestion.…”
Section: Resultsmentioning
confidence: 99%
“…A peroxide pretreatment enhance enzymatic conversion through oxidative delignification and a decrease in cellulose crystallinity [10]. Increased lignin solubilization and cellulose availability were observed after a peroxide pretreatment of wheat straw [11], Douglas fir [12], and oak [13]. Ozonation is another attractive pretreatment method that does not leave strong acidic, basic, or toxic residues in the treated material [14].…”
Section: Introductionmentioning
confidence: 97%
“…Taking the typical feedstock of corncob as an example, approximately 75% lignin was removed, and only 38% hemicellulose was removed (Su et al, 2015). Besides, H 2 O 2 supplementation (1.6%) in the diluted sulfuric acid (0.1%) was investigated to pretreat oak at 170°C, in which hemicellulose removal was improved, and delignification was not increased much (Kim et al, 2001). Thus, the reactions of hemicellulose and lignin with PHP were uniquely different with those of the alkaline hydrogen peroxide and the diluted acid plus H 2 O 2 .…”
Section: Effects Of H 3 Po 4 Proportionmentioning
confidence: 99%